Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/s2222-1808(13)60059-6
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of Helicobacter pylori infection among asymptomatic healthy Omani blood donors

Abstract: Objective: To investigate the prevalence of Helicobacter pylori (H. pylori) infection, a crosssectional epidemiological study, based on the age and gender-specific seroprevalence of H. pylori antibodies in asymptomatic healthy Omani blood donors attending the SQUH blood bank. Methods: Analysis of the sera from 133 apparently healthy subjects, based on the serological determination of the IgM, IgG and IgA antibodies against H. pylori, was carried out using a commercially available kit ELISA (NovaLisa, NovaTec, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
2
7
3
Order By: Relevance
“…There are no studies in the same age group in Oman to compare this result with. However, a recent seroprevalence study on adult blood donors between 18 and 50 years of age estimated prevalence to be 68% among 133 blood donors . They documented increment in seroprevalence with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no studies in the same age group in Oman to compare this result with. However, a recent seroprevalence study on adult blood donors between 18 and 50 years of age estimated prevalence to be 68% among 133 blood donors . They documented increment in seroprevalence with age.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori infection prevalence in Omani adults and children is not known. A recent study reported seroprevalence of 68% out of 133 blood donors . No data is available regarding H. pylori infection prevalence in Omani children.…”
mentioning
confidence: 99%
“…While the majority of the studies included in this review did not find a significant relationship between gender and rate of infection, two studies by Soltani et al [22] and Al-Balushi et al [29] found that seropositivity was more widespread in male than in female participants.…”
Section: Risk Factors For H Pylori Infectionmentioning
confidence: 79%
“…According to previous studies, Khat chewing had a positive association with gastrointestinal disorders such as dental problems, gastritis and constipation 6 . In a study conducted on healthy Omani blood donors, the overall prevalence for Helicobacter pylori was 69.5% 25 . In a study from India, 254 individuals were screened for Helicobacter pylori which were positive in 56.7% asymptomatic individuals 26 .…”
Section: Discussionmentioning
confidence: 99%